WANITA CANTIK DAN KEJATUHAN PEMERINTAHAN HEBAT DALAM FILEM “TUN FATIMAH” (1962): A BEAUTIFUL WOMAN AND THE DOWNFALL OF A GREAT RULER IN THE FILM “TUN FATIMAH” (1962) - Ayu Haswida Abu Bakar (Jurnal Pengajian Melayu (JOMAS), 2021)
Abstract Beautiful women have often been associated with great men of authority and governance in various kingdoms. However, according to scholars, the beautiful female subject also serves as a domineering figure that monopolises the man himself. She can also be a contributing factor towards the downfall of an empire and the world of the man she exists in. For instance, this phenomenon occurred during certain Chinese dynasties. Hence, this research, using the film titled “Tun Fatimah” (1962), focuses on studying and analysing the relationship between the beauty of Tun Fatimah – the daughter of the “Dato‟ Bendahara” of Malacca and the wife of Tun Ali – and the creation of a “sultan” (king), who was still a bachelor and governed tyrannically. Subsequently, history witnessed the king‟s downfall as a ruler in the larger context of the Malay World. It also led to fissures within the great Malaccan sultanate. This research utilises a qualitative approach, focusing on the detailed textual-narrative analysis of the film, supported by the epistemology of desire. Findings show that Tun Fatimah‟s beauty, which was befitting as queen for the Malaccan sultanate, is the main factor in contributing to the libido imbalance of the king and the weakness of hegemonic masculinity in the empire. The imbalance triggered the king‟s irrationality as shown through his emotions such as the thirst for vengeance, anger, jealousy, guilt and regret. In conclusion, the factors proved they did contribute fully to creating a tyrannical Malaccan king. Keywords: Southeast Asian cinema, Malaysian cinema, Tun Fatimah, epistemology of desire beautiful woman, hegemonic masculinity. Abstrak Wanita cantik sering dikaitkan dengan dominasi lelaki hebat seperti pemegang autori dan pemerintah hebat sebuah kerajaan. Wanita cantik mengikut para sarjana bertindak sebagai indeks objek dominasi dan monopoli lelaki yang bersifat subjek. Sungguhpun begitu, wanita cantik adalah faktor penyumbang kepada kejatuhan sebuah empayar dan dunia lelaki hebat tersebut. Seperti kejatuhan beberapa Dinasti China dahulu. Fokus kajian adalah mengkaji dan menganalisa hubungkait antara kecantikan Tun Fatimah, anak Dato Bendahara Melaka dan isteri kepada Tun Ali, dalam filem Tun Fatimah (1962), dengan pembentukan figura Sultan Melaka yang masih tidak mempunyai permaisuri, sebagai pemerintahan zalim dan keruntuhan kewibaan Sultan sebagai pemerintah yang hebat di alam Melayu. Justeru, menyumbang kepada kelemahan Kerajaan Kesultanan Melaka. Kajian ini menggunakan pendekatan kualitatif yang bersifat analisa tekstual-naratif filem Tun Fatimah (1962), melalui Pendekatan Epistemology of Desire. Hasil kajian yang dirumuskan adalah kecantikan Tun Fatimah yang sifatkan sebagai setaraf dengan tahap seorang permaisuri Kerajaan Melaka adalah penyumbang utama kepada proses ketidakseimbangan libido kelakian Sultan dan kelemahan hegemonic masculinity Kerajaan Melaka. Justeru, proses ketidakseimbangan libido ini adalah faktor pemangkin kepada berlakunya tahap ketidakwarasan emosi Sultan yang diangkat melalui unsur emosi dendam, marah, cemburu, bersalah dan menyesal. Maka dengan itu, kelima-lima unsur ini secara kukuh menyumbang sepenuhnya kepada proses pembentukan figura Sultan Melaka ini sebagai seorang pemerintah yang zalim. Kata Kunci: Sinema Asia Tenggara, Sinema Malaysia, Tun Fatimah, epistemology of desire, Wanita Cantik, hegemonic masculinity.